ChemInform Abstract: Synthesis and Characterization of Kesterite Cu2ZnSnTe4 via Ball‐Milling of Elemental Powder Precursors. Issue 41 (September 2016) - Pareek, Devendra; Balasubramaniam, K. R.; Sharma, Pratibha
Abstract: The title compound is synthesized by ball‐milling of powder mixtures of Cu, Zn, Sn, and Te (planetary ball mill, 450 rpm, 30 h).